Rola polskich serii książkowych na przykładzie serii Państwowego Wydawnictwa „Iskry” w latach 1956-1992 - Kowalewska , Urszula (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The author of the text presents various thematic book series published by the National Publishing House “Iskry”, existing in Poland from 1952 to 1992. It used to publish literature for young people at the age of 16 to 18, first of all books of contemporary writers, future writers, reporters and popularizers of science. In the activity of “Iskry”, different series and cycles became the most important. They were introduced on the publishing market in 1956. The wide range of series was very rich and covered social-political literature, ideological literature, and travel, memory, report, adventure, sensational, science-fiction and satirical literature. The important role of book series in popularization of reading among young generations is also discussed in this article. The role of book series in molding of reading habits between children and youth seems to be important and essential. Deciding for publishing of book series, “Iskry” became responsible for the best choice of titles connected with them. It is very useful for an unexperienced reader because it helps doing choice of the best literature.